Kunst & Zwalm. - Van Mulders, Wim (Zwalm : vzw Boem, 2009)
Bechameil, Jean ; Dheedene, Stefaan ; Ewen, Luc ; Feipel, Martine ; Frantz, Jerry ; Frantzen, Christian ; Jacobs, Roel ; Manders, Mark ; Moens, Rik ; Nys, Sophie ; Quetsch, Roland ; Schacht, Kelly ; Van San, Tamara ; Vangrunderbeek, Dimitri
boek